Estrus and fertility responses in acyclic ewes treated with short, medium or long-term GnRH-PGF2α-GnRH protocols supplemented with intra-vaginal progesterone therapy - HARIOM, HARIOM; SINGH, HARPREET; DUTT, RAVI; RANGA, L C (The Indian Journal of Animal Sciences, 2022)
The present study was conducted with the aim to compare the effectiveness of the short-term (5 days), moderateterm (8 days) and long-term (12 days) progesterone therapy in the form of intravaginal AVIKESIL-S® progesterone sponge developed by CSWRI, Avikanagar (Rajasthan), during modified GnRH-PGF2α-GnRH treatments during non-breeding season (May-July) in crossbred (Nali×Rambuillet) ewes. The seasonal anestrus ewes were enrolled into four groups. In Group 1 (n=50), ewes were treated with GnRH on day 0, PGF2α on day 5, and second GnRH on day 7 plus progesterone supplementation with intravaginal progesterone sponge from day 0 to day 5 while in Group-2 (n=50), ewes were treated with GnRH on day 0, PGF2α on day 8, and second GnRH on day 9 plusprogesterone supplementation with intravaginal progesterone sponge from day 0 to day 8. Further, in Group 3(n=50), ewes were treated with GnRH on day 0 and PGF2α on day 12 and second GnRH on day 13 plus progesteronesupplementation with intravaginal AVIKESIL-S® sponge from day 0 to day 12. Group 4 (n=50), comprised ofuntreated control animals. Results showed that estrus synchronization rate (%) was significantly higher in Group 2and Group 3 in comparison to Group 4 (control). There was significant difference in the duration of estrus, pregnancy rate, lambing rate in Group 2 as compared to Group 4 (control) but prolificacy and fecundity were not statistically significant (p>0.01) among the groups during out of breeding season. Thus, modified Ovsynch protocol with 8-day progesterone therapy is better for augmenting fertility in crossbred ewes during non-breeding season.